MEDIA LEARNING FOR EARLY CHILDHOOD IN EARLY CHILDHOOD EDUCATION - Mardhatillah Mardhatillah (Sensei International Journal of Education and Linguistic, 2021)
Early Childhood Education is an effort to stimulate and stimulate children from birth to the age of six which is carried out by providing educational stimuli to help the growth and development of children, both physically and spiritually so that children are ready to enter further education. Early childhood is a group that is in a process of growth and development that is unique, namely patterns of growth and development, intelligence, social-emotional, language, and communication that are specific to the child's level of growth and development. Media in an activity can be interpreted as anything that can be used to channel messages or lesson content, stimulate thoughts, feelings, attention, and the ability of children so that they can encourage the achievement of the process of activities stimulated by the teacher. The use of technological media can have a positive impact, in other words, the use of multimedia or animation as a learning tool and a teacher's tool in carrying out the activity process.